Spectrum of renal diseases in the elderly, above age 50 - Pratishtha Sengar; Pallav Gupta (Wolters Kluwer Medknow Publications, 2022)
Background: The spectrum of kidney diseases varies in the elderly population with frequent inconsistencies between clinical presentation and histopathological diagnosis. The immunofluorescence (IF) may provide additional information in such situations. Aims: The purpose was to study the spectrum of kidney diseases in patients above 50 years undergoing renal biopsy and utility of light chain (LC) IF in the diagnosis. Settings and Design: This was a retrospective, crosssectional, singlecenter-based study. Material and Methods: The clinical details, histopathological findings, and LC IF pattern in native renal biopsy of patients above 50 years were noted. Statistical Analysis: Continuous variables were presented as mean ± standard deviation (SD). Categorical variables were expressed as frequencies and percentages. Results: A total of 205 patients were included in the study. The most common clinical presentation was acute kidney injury/rapidly progressive glomerulonephritis (AKI/RPGN) (49%). Glomerular diseases (72%) were more common. Crescentic glomerulonephritis (21%) and membranous nephropathy (MN) (19%) were the most common glomerulopathy. LC restriction was observed in LC cast nephropathy (LCCN), primary amyloidosis, and LC also helped in classifying the cases of MPGN-type morphology. Conclusions: AKI/RPGN was the most common indication for renal biopsy in patients above 50 years. Crescentic GN and MN were the frequent glomerular pathology. LC IF is a useful adjunctive tool to classify various renal diseases.